Understanding Global Market Development Strategies: A Qualitative Inquiry into Business, Public Administration Strategy Adaptation and International Supply Chain Management in the Globalization Era - Prasodjo, Tunggul (Manunggal Halim Jaya, 2023)
This research provides a comprehensive exploration of global market development strategies, business strategy adaptation, and international supply chain management in the globalization era. The study aims to understand the complex interplay of factors shaping contemporary business practices and to derive insights for enhancing competitiveness in international markets. The research adopts a qualitative inquiry approach, synthesizing existing literature and scholarly perspectives to analyze the phenomena under investigation. Through a thorough review of relevant literature, the study identifies key themes and theoretical frameworks, providing a nuanced understanding of global business dynamics. The findings highlight the diverse strategies employed by firms to navigate international markets, adapt to changing business environments, and manage global supply chain networks effectively. Insights gleaned from the research underscore the importance of strategic adaptation, dynamic capabilities, and collaboration in driving business success in the global marketplace. Moreover, the study elucidates the significance of supply chain resilience, agility, and digitalization in mitigating risks and capitalizing on opportunities in an interconnected world. The implications of the research extend to both theoretical and managerial domains, informing evidence-based strategies for sustainable growth and competitiveness in the globalization era.